Dopamine Levels Induced by Substance Abuse Alter Efficacy of Maraviroc and Expression of CCR5 Conformations on Myeloid Cells: Implications for NeuroHIV - Matt, Stephanie M.; Nickoloff-Bybel, Emily A.; Rong, Yi; Runner, Kaitlyn; Johnson, Hannah; O’Connor, Margaret H.; Haddad, Elias K.; Gaskill, Peter J. (Frontiers in Immunology, 2021)
Despite widespread use of antiretroviral therapy (ART), HIV remains a major public health issue. Even with effective ART many infected individuals still suffer from the constellation of neurological symptoms now known as neuroHIV. These symptoms can be exacerbated by substance abuse, a common comorbidity among HIV-infected individuals. The mechanism(s) by which different types of drugs impact neuroHIV remains unclear, but all drugs of abuse increase central nervous system (CNS) dopamine and elevated dopamine increases HIV infection and inflammation in human myeloid cells including macrophages and microglia, the primary targets for HIV in the brain. Thus, drug-induced increases in CNS dopamine may be a common mechanism by which distinct addictive substances alter neuroHIV. Myeloid cells are generally infected by HIV strains that use the chemokine receptor CCR5 as a co-receptor, and our data indicate that in a subset of individuals, drug-induced levels of dopamine could interfere with the effectiveness of the CCR5 inhibitor Maraviroc. CCR5 can adopt distinct conformations that differentially regulate the efficiency of HIV entry and subsequent replication and using qPCR, flow cytometry, Western blotting and high content fluorescent imaging, we show that dopamine alters the expression of specific CCR5 conformations of CCR5 on the surface of human macrophages. These changes are not affected by association with lipid rafts, but do correlate with dopamine receptor gene expression levels, specifically higher levels of D1-like dopamine receptors. These data also demonstrate that dopamine increases HIV replication and alters CCR5 conformations in human microglia similarly to macrophages. These data support the importance of dopamine in the development of neuroHIV and indicate that dopamine signaling pathways should be examined as a target in antiretroviral therapies specifically tailored to HIV-infected drug abusers. Further, these studies show the potential immunomodulatory role of dopamine, suggesting changes in this neurotransmitter may also affect the progression of other diseases.